Estetika Alih Wahana Kisah Putri Karang Melenu Ke Bentuk Ukiran Tambak Karang Nungkul - Ulum Janah (Faculty of Letters Universitas Balikpapan, 2022)
Transferring is an activity of transferring and changing from one form of work to another. One form of transfer of rides can be found, namely the story of Princess Karang Melenu to the Carving of the Karang Nungkul Pond which is usually carried out during the Beluluh Sultan traditional procession during Erau. The transfer is carried out by utilizing aesthetic theory and comparative literary approaches to analyze the findings as well as to find out the comparison between the two objects, both in general and in their aesthetic presentation. Furthermore, from this comparison it can be seen the benefits of the transfer. The results of the research are generally obtained from the comparison of omissions, subtractions, additions, and replacements of images from the story of Princess Karang Melenu into nungkul coral carvings. Meanwhile, in terms of aesthetic presentation, the results obtained are in the form of wholeness, prominence, and balance which refers to the ideology and identity of the Kutai Kartanegara Sultanate. This transfer is also useful in strengthening or strengthening the roots of Kutai culture and can be used as a medium of learning in schools.